Data policies and data archives as prerequisites of reproducible published research in economics journals - Vlaeminck, Sven (Septentrio Conference Series, 2014)
>> See video of presentation (19 min.) In economics - as in many other branches of the social sciences- collaboratively working on data and sharing data is not very common, yet. This is also reflected in the professions’ journals, where policies on data management and data sharing currently exist for a small minority of journals only. I would like to introduce the presentation with some empirical results of a survey, in which economists working for the project EDaWaX (European Data Watch, a project funded by the German Research Foundation) analysed the data sharing behaviour of 488 US and European applied economists. Subsequently we give an overview on data policies of journals in economics and business studies. In the course of the EDaWaX project, the data policies in a sample of more than 300 economics journals have been analysed. The talk suggests guidelines for data policies aiming to foster replication of published research and presents some characteristics of journals equipped with those data policies as well as the status quo in disseminating underlying research data of empirically based articles. Against this analytical background the talk identifies some challenges associated with the current e-infrastructure for providing publication-related research data by journals. The presentation also shows a technical solution for some of these challenges. In particular, the talk presents a pilot application for a publication-related data archive for scholarly journals in the social sciences, which has been developed in the first funding phase of the EDaWaX-project. The aim of this open source tool is to empower editors of scholarly journals to easily manage research data for empirically based articles in their journals. The application mainly targets open research data but is also capable of interlinking data and publications even in the case of confidential or proprietary data. In conclusion the talk outlines the further development of our application and sketches other tasks of the project’s second funding phase. More information on the project is available on www.edawax.de